2022
DOI: 10.3390/land11101720
|View full text |Cite
|
Sign up to set email alerts
|

Installing Flower Strips to Promote Pollinators in Simplified Agricultural Landscapes: Comprehensive Viability Assessment in Sunflower Fields

Abstract: The installation of flower strips in simplified agricultural landscapes has been promoted as a tool to improve pollination services. While the effectiveness of flower strips in increasing pollinator visitation and yield is well-established, the social and economic feasibility of this measure remains unclear. Here, we evaluated the economic efficiency and social feasibility of installing flower strips to promote pollination under different scenarios of subsidy. A 2-year experiment was implemented by comparing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Melliferous aromatic crops could act as an attractive spot for pollinators. In this regard, an experiment showed that bee visitation to sunflower heads increased due to flower strips containing 12 melliferous species, including Salvia pratensis [ 144 ]. In intensive agricultural areas, ensuring flower strips and semi-natural habitats (which include Lamiaceae species) in the vicinity of crops with the purpose of creating a refuge and attraction point for bees can result in more visits to the flowers of the nearby crops, therefore increasing seed yield—as demonstrated for sunflower crops [ 144 , 145 ].…”
Section: Practical Implications Of the Volatiles Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melliferous aromatic crops could act as an attractive spot for pollinators. In this regard, an experiment showed that bee visitation to sunflower heads increased due to flower strips containing 12 melliferous species, including Salvia pratensis [ 144 ]. In intensive agricultural areas, ensuring flower strips and semi-natural habitats (which include Lamiaceae species) in the vicinity of crops with the purpose of creating a refuge and attraction point for bees can result in more visits to the flowers of the nearby crops, therefore increasing seed yield—as demonstrated for sunflower crops [ 144 , 145 ].…”
Section: Practical Implications Of the Volatiles Emissionmentioning
confidence: 99%
“…In this regard, an experiment showed that bee visitation to sunflower heads increased due to flower strips containing 12 melliferous species, including Salvia pratensis [ 144 ]. In intensive agricultural areas, ensuring flower strips and semi-natural habitats (which include Lamiaceae species) in the vicinity of crops with the purpose of creating a refuge and attraction point for bees can result in more visits to the flowers of the nearby crops, therefore increasing seed yield—as demonstrated for sunflower crops [ 144 , 145 ]. A meta-analysis provided increasing evidence that flower strips improve pest control and seed yield in the adjacent fields [ 146 ], indicating that this is a justified path of research.…”
Section: Practical Implications Of the Volatiles Emissionmentioning
confidence: 99%
“…Additionally, sunflower resilience landscapes may include companion plantings, such as planting other flowers and vegetables that can help protect sunflowers from pests and diseases. Wild sunflowers may also incorporate water conservation strategies, such as using drought-tolerant plants and rainwater harvesting in European areas which have a similar climate to the US [9].…”
Section: Sunflower Potential Advantages For New Landscape Designsmentioning
confidence: 99%